Building Early Literacy through the Evaluation of Indonesian Language Learning Methods in Elementary Schools: A Systematic Literature Review - Putri Hana Pebriana; Ulfa Ramadhani; Rahmiatul Fitri; Khairunnisakh Jailani; Dora Elfita Velonia; Salsa Slovenia; Mhd.Devri Yanda (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to evaluate the effectiveness of Indonesian language learning methods in developing early literacy among elementary school students. Effective learning plays a crucial role in the development of children’s language skills. The Systematic Literature Review (SLR) method was employed to analyze 25 relevant scientific articles obtained from the SINTA and Google Scholar databases, with publication periods ranging from 2018 to 2023. The results of the analysis indicate that project-based learning approaches and the use of digital technology, such as interactive learning applications, have significant positive impacts on students’ reading and writing skills. Despite these advancements, challenges such as limited teacher training and inadequate access to technology remain obstacles to the effectiveness of these methods. This study concludes that the implementation of innovative learning methods and adequate educational support are essential for improving literacy among elementary school students. Recommendations for stakeholders include enhancing teacher training programs and providing sufficient resources to support more effective learning methods.